Interdisciplinarity and Intradisciplinarity in Family Pedagogy - Opozda, Danuta (Paedagogia Christiana, 2015)
The article deals with the problem of the interdisciplinarity and the intradisciplinarity in family pedagogy. This text refers to the methodological issues of family pedagogy, particularly, its subject of study. The problem of specialization and integration of knowledge about the upbringing in the family is presented in the article. The requirement of the interdisciplinarity and the intradisciplinarity in family pedagogy is substantially connected with the development of the pedagogical knowledge about the upbringing in the family – the dynamic knowledge, which is the result of the dialogue that is sustained inside and outside the discipline. The following question may be raised: is in statu nascendi of the family pedagogy rather its privilege or burden?